Differences between STAD and TSTS Cooperative Learning Models on Mathematics Learning Outcomes for Class X Students at Sultan Iskandar Muda Private High School - Waruwu, Novy Any; Sihombing, W L (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to evaluate the differences in mathematics learning outcomes between students taught using two different cooperative learning models: Student Teams Achievement Division (STAD) and Two Stay Two Stray (TSTS). This research employs a quasi-experimental method with a quantitative approach. Conducted at SMA Swasta Sultan Iskandar Muda Medan, the study involved two sample classes selected using purposive sampling technique. Class X IPA 7 was designated as Experiment I with the implementation of the TSTS model, while class X IPA 5 served as Experiment II with the STAD model. Data were collected through observation sheets and learning outcome tests consisting of 5 essay questions. Data analysis was performed using t-test with the Independent Sample T-Test technique via IBM SPSS 27 software. The results indicated that the average score of the class taught using the TSTS model was 81.00, while the class taught using the STAD model scored 74.27. Hypothesis testing showed a  of 3.128 and a  value of 1.672 with a significance level of 0.003 0.05, leading to the rejection of H0 and the acceptance of Ha. In conclusion, the mathematics learning outcomes of students taught with the TSTS cooperative learning model are higher compared to those taught with the STAD cooperative learning model.